Korelasi Materi PAI dengan Tingkah Laku Keagamaan Siswa - Uun Kurnaesih (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2017)
Student religious behavior, in addition to being influenced by family education, discipline and religious habits that exist in the student community, is also influenced by Islamic Religious Education materials taught in schools. Students' understanding of Islamic religious education materials taught will foster religious attitudes in students, so students are encouraged to behave in accordance with the religious understanding of religious teachings. The religious behavior of students will be better if students' understanding of religious education materials in the study is good. The problems discussed in this study are: Is there a correlation between Islamic religious education materials with religious behavior of students in I Anyer High School? This research aims: to find out the correlation between Islamic religious education material with the religious behavior of students in I Anyer High School. This study uses correlational techniques, with a population of all grade 2 students of SMA Negeri I Anyer, in 2014/2015, amounting to 257 students. While the sample in this study, amounting to 25% of the population, totaling 64 students. Data about the PAI material taught at the school was obtained through the Anyer I High School curriculum documentation, and a questionnaire consisting of 88 question items. while the religious behavior of students was obtained from the results of a questionnaire consisting of 44 item items. Data from the field study were processed and analyzed using Spearman rank correlation analysis. The results of data analysis obtained P = 0.62. Furthermore, significance was tested using the formula t, because of N> 30. Then obtained tcount = 7.77. These results were then consulted on a table with a significance level of 5%, then obtained a table = 1.96. These results indicate that tcount is greater than ttable (th> tt). So, it can be concluded that there is a correlation between Islamic religious education material with the religious behavior of students in Anyer I Public High School. Thus the alternative hypothesis (Ha) is accepted.